Adolescent and adult risk-taking in virtual social contexts - Haddad, Anneke D. M.; Harrison, Freya; Norman, Thomas; Lau, Jennifer Y.F. (Frontiers in Psychology, 2014)
There is a paucity of experimental data addressing how peers influence adolescent risk-taking. Here, we examined peer effects on risky decision-making in adults and adolescents using a virtual social context that enabled experimental control over the peer “interactions”. 40 adolescents (age 11-18) and 28 adults (age 20-38) completed a risk-taking (Wheel of Fortune) task under 4 conditions: in private; while being observed by (fictitious) peers; and after receiving ‘risky’ or ‘safe’ advice from the peers. For high-risk gambles (but not medium-risk or even gambles), adolescents made more risky decisions under peer observation than adults. Adolescents, but not adults, tended to resist ‘safe’ advice for high-risk gambles. Although both groups tended to follow ‘risky’ advice for high-risk gambles, adults did so more than adolescents. These findings highlight the importance of distinguishing between the effects of peer observation and peer advice on risky decision-making.